Neurophysiological observations on corticospinal projections to the upper limb in subjects with Rett syndrome. Issue 10 (October 1990) - Eyre, J A; Kerr, A M; Miller, S; O'Sullivan, M C; Ramesh, V
Abstract : The aim of the present study was to investigate the excitability of corticospinal neurons and the integrity of their projections to the alpha motor neurons through the corticospinal tract in subjects of different ages with Rett syndrome. Electromagnetic stimulation of the motor cortex and cervical motor roots was used to evoke motor action potentials in the biceps brachii and hypothenar muscles. The phasic stretch reflex in the biceps brachii was also recorded to study the excitability of spinal alpha motor neurons. Motor cortex stimulation evoked motor action potentials at low threshold and with abnormally short latencies and prolonged durations. In contrast cervical motor root stimulation resulted in responses of normal latency and duration. The phasic stretch reflex had a low threshold, short latency and prolonged duration. It is concluded that in Rett syndrome the corticospinal pathway is intact. The results suggest disordered synaptic control of the Betz cell of the motor cortex and/or the spinal alpha motor neuron, although the involvement of the latter might be a consequence of dysfunction in supraspinal descending motor pathways.